IMPLEMENTASI WAJIB LAPOR KETENAGAKERJAAN PERUSAHAAN PADA INDUSTRI PERBANKAN (STUDI KASUS KOTA SAMARINDA) - Pratama, Rio Arif; Herdiawan, Herdiawan; Hasmiati, Rahmatullah Ayu (PSHPM Untag Semarang, 2025)
The banking industry is one of the companies that has a big impact on the development and economic progress of a country. In carrying out the operational activities of the banking industry company, of course there are company obligations in running the company, one of which is that the company must report employment data to the East Kalimantan province's labor and transmigration office. However, in reality, in the field, many companies have not carried out mandatory employment reporting. The aim of the research is to determine the implementation, supervision, and investigation of mandatory company employment reporting in the banking industry in the city of Samarinda. The research method uses empirical, juridical, literature, and field approaches and is analyzed descriptively qualitatively. Results and discussion show that 16 out of 20 banking industry companies have implemented mandatory corporate employment reporting. The company's legal compliance and awareness of statutory regulations have been implemented quite well. Supervision and investigation were also carried out well. The limited number of supervisors is still weak; 1 out of 15 supervisors can only supervise 5 companies once a month. Banking industry companies must be aware of the regulations of Law Number 7 of 1981 concerning mandatory employment reporting so that employment reporting obligations can be carried out optimally.